A Frog-Derived Immunomodulatory Peptide Promotes Cutaneous Wound Healing by Regulating Cellular Response - He, Xiaoqin; Yang, Yang; Mu, Lixian; Zhou, Yandong; Chen, Yue; Wu, Jing; Wang, Yipeng; Yang, Hailong; Li, Min; Xu, Wei; Wei, Lin (Frontiers in Immunology, 2019)
Wound healing-promoting peptides exhibit excellent therapeutic potential in regenerative medicine. However, amphibian-derived wound healing-promoting peptides and their mechanism of action remain to be further elucidated. We hereby characterized a novel wound healing-promoting peptide, Ot-WHP, derived from Chinese concave-eared frog Odorrana tormota. It efficiently promoted wound healing in a mouse model of full-thickness wounds. Ot-WHP significantly increased the number of neutrophils in wounds, and modestly promoted neutrophil phagocytosis and phorbol myristate acetate (PMA)-induced neutrophil extracellular trap formation. Ot-WHP also significantly increased the number of macrophages in wound sites, and directly induced chemokine, cytokine and growth factor production in macrophages by activating mitogen-activated protein kinases (MAPKs) and nuclear factor-κB (NF-κB) signaling pathways. Of note, Ot-WHP did not act as a chemoattractant for neutrophils and macrophages, suggesting its chemotactic activity depends on inducing chemoattractant production in macrophages. Besides, Ot-WHP directly promoted keratinocyte migration by enhancing integrin expression and cell adhesion. In addition, Ot-WHP significantly enhanced the cross-talk between macrophages and keratinocytes/fibroblasts by promoting keratinocyte/fibroblast proliferation, and fibroblast-to-myofibroblast transition despite of no direct effects on keratinocyte/fibroblast proliferation, and fibroblast differentiation. Collectively, Ot-WHP directly elicited the production of regulatory factors in macrophages, consequently initiated and accelerated the inflammatory phase by recruiting neutrophils and macrophages to wounds, in turn enhanced the cross-talk between macrophages and keratinocytes/fibroblasts, additionally promoted keratinocyte migration, and finally promoted cutaneous wound healing. Our findings provide a promising immunomodulator for acute wound management and new clues for understanding the mechanism of action of amphibian-derived wound-promoting peptides.